Chromosome 19 microRNAs exert antiviral activity independent from type III interferon signaling. (January 2018) - Bayer, Avraham; Lennemann, Nicholas J.; Ouyang, Yingshi; Sadovsky, Elena; Sheridan, Megan A.; Roberts, R. Michael; Coyne, Carolyn B.; Sadovsky, Yoel
Abstract: Introduction: Cultured primary human trophoblasts (PHT), derived from term placentas, are relatively resistant to infection by diverse viruses. The resistance can be conferred to non-trophoblastic cells by pre-exposing them to medium that was conditioned by PHT cells. This antiviral effect is mediated, at least in part, by microRNAs (miRNA) expressed from the chromosome 19 microRNA cluster (C19MC). Recently we showed that PHT cells and cells pre-exposed to PHT medium are also resistant to infection by Zika virus (ZIKV), an effect mediated by the constitutive release of the type III interferons (IFN) IFN lambda-1 and IFN lambda-2 in trophoblastic medium. We hypothesized that trophoblastic C19MC miRNA are active against ZIKV, and assessed the interaction of this pathway with IFN lambda-1 - mediated resistance. Methods: Term PHT cells were cultured using standard techniques. An osteosarcoma cell line (U2OS) was used as non-trophoblastic cells, which were infected with either ZIKV or vesicular stomatitis virus (VSV). Trophoblastic extracellular vesicles (EVs) were produced by gradient ultracentrifugation. RT-qPCR was used to determine viral infection, cellular or medium miRNA levels and the expression of interferon-stimulated genes. Results: We showed that C19MC miRNA attenuate infection of U2OS cells by ZIKV, and that C19MC miRNA or exosomes that contain C19MC miRNA did not influence the type III IFN pathway. Similarly, cell exposure to recombinant IFN lambda-1 had no effect on miRNA expression, and these pathways did not exhibit synergistic interaction. Discussion: PHT cells exert antiviral activity by at least two independent mechanisms, mediated by C19MC miRNA and by type III IFNs. Highlights: The expression of C19MC miRNA attenuates ZIKV infection. Trophoblastic exosomes do not induce IFN-stimulated genes. Type III IFNs and C19MC miRNA act independently to lessen viral replication.